Social Activities in Improving the Quality of Post-Retirement Life - Suparmi, Suparmi; Wulan, Bunga Dwi; Artikasari, Anisa Dian (International Journal of Education, Information Technology, and Others, 2024)
Humans in their lives face events that show transition processes, which vary from childhood to old age. Retirement is three things that are lost, namely routine activities, coworkers, and lost time interacting with coworkers. The retirement period experiences a change in routine, namely going to work in the morning and returning home in the afternoon or evening. These activities change and tend to have a lot of free time because they have entered retirement. The happiness of the elderly hopes to live happily and prosperously in old age, spending the rest of their lives with their beloved family. This research aims to find out what activities can improve the overall quality of life of elderly people. This research method is a Literature Review, which is carried out by searching for articles online using Publish and Perish then involves reading and reviewing existing literature to find related research. The results of this research are that social activities such as religion, agriculture, social gatherings, arts and culture, and the use of social media can improve a person's quality of life.